High temperature suppressed SSC self-renewal through S phase cell cycle arrest but not apoptosis - Jia Wang; Wei-Jun Gao; Shou-Long Deng; Xiang Liu; Hua Jia; Wen-Zhi Ma (Stem Cell Research & Therapy, 2019)
Abstract Background High temperature has a very adverse effect on mammalian spermatogenesis and eventually leads to sub- or infertility through either apoptosis or DNA damage. However, the direct effects of heat stress on the development of spermatogonial stem cells (SSCs) are still unknown because SSCs are rare in the testes. Methods In the present study, we first used in vitro-cultured SSCs to study the effect of heat shock treatment on SSC development. Then, we used RNA-Seq analysis to identify new genes or signalling pathways implicated in the heat stress response. Results We found that 45 min of 43 °C heat shock treatment significantly inhibited the proliferation of SSCs 2 h after treatment but did not lead to apoptosis. In total, 17,822 genes were identified by RNA-Seq after SSC heat shock treatment. Among these genes, we found that 200 of them had significantly changed expression, with 173 upregulated and 27 downregulated genes. The number of differentially expressed genes in environmental information processing pathways was 37, which was the largest number. We screened the candidate JAK-STAT signalling pathway on the basis of inhibition of cell cycle progression and found that the JAK-STAT pathway was inhibited after heat shock treatment. The flow cytometry results further confirmed that heat stress caused S phase cycle arrest of SSCs. Conclusion Our results showed that heat shock treatment at 43 °C for 45 min significantly inhibited SSC self-renewal through S phase cell cycle arrest but not apoptosis.